Postcolonial Traumas
XII, 235 p.
Keywords: This collection of essays explores some new possibilities for understanding postcolonial traumas. It examines representations of both personal and collective traumas around the globe from Palestinian, Caribbean, African American, South African, Maltese, Algerian, Indian, Australian and British writers, directors and artists.